STRUCTURAL CHANGES OF INTERNAL ORGANS IN DOMESTIC CAT AND DOG AT OBESITY CAUSED BY DIABETES MELLITUS - Lokes-Krupka, T. P.; Tsvilichovsky, M. I.; Kanivets, N. S.; Kravchenko, S. O.; Burda, T. L. (Scientific Progress & Innovations, 2020)
The results of ultrasonographic examinations of the internal organs of domestic dogs and cats with obesi-ty, which have developed as a result of diabetes mellitus, have been presented in the article. The significant amount of adipose tissue was revealed in cats and dogs suffering from diabetes mellitus with symptoms simi-lar to alimentary obesity, which changed the quality of ultrasonographic picture. A slight uniform, diffuse increase of the echogenicity of the liver parenchyma was registered. In most diseased animals, shading in remote organ areas was visualized. The typical symptoms of cholestasis and cholecystitis were revealed, namely a full, slightly enlarged gallbladder caused by hyporexia. Increasing the parenchyma granularity, thickening and moderate increasing the liver capsule echogenicity, depleting the liver vascular pattern were registered in experimental cats and dogs. The kidneys of domestic cats with alimentary obesity and cats with diabetes mellitus and obesity had the following compatible sonographic characteristics: bean-shaped kid-neys, with clear contours and a smooth surface. In diabetic domestic dogs, the kidneys were bean-shaped with smooth clear contours, and typical unechogenic pattern of the medullary area. The renal medulla was echogenic, and cortical-medullary differentiation was well expressed. The renal pelvis had no sonographic signs of deformity. The main difference between animals with diabetes mellitus at the background of obesity, as compared with cats and dogs with alimentary obesity, were more pronounced dystrophic changes of the pancreas. The imaging of internal organs was worse because of excessive fat layer. At the same time, the signs of chronic pancreatitis were registered in more than half of domestic cats (n=8) and dogs (n=5) dis-eased with diabetes mellitus. Decreasing the pancreas size, various degrees of the parenchyma uneven echo-genicity, nodular echo-structure, with acoustic shadows as a result of calcification and cicatrization, as well as uneven dilating of pancreatic ducts were detected. Ultrasonographic picture of the internal organs of companion animals in case of obesity because of diabetes mellitus coordinated with the results of biochemi-cal examination.